2013
DOI: 10.1111/1471-0528.12278
|View full text |Cite
|
Sign up to set email alerts
|

Elective caesarean section at 38 weeks versus 39 weeks: neonatal and maternal outcomes in a randomised controlled trial

Abstract: Population Women with uncomplicated pregnancies, a single fetus, and a date of delivery estimated by ultrasound scheduled for delivery by elective caesarean section.Methods Perinatal outcomes after elective caesarean section scheduled at a gestational age of 38 weeks and 3 days versus 39 weeks and 3 days (in both groups AE2 days).Main outcome measures The primary outcome was neonatal intensive care unit (NICU) admission within 48 hours of birth. Secondary outcomes were neonatal depression, NICU admission withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 23 publications
3
90
1
Order By: Relevance
“…However using the Chi square test (p=0.705) and there was no significant relation between weeks of gestation and the rate of NICU admission. In a study done by Glavind J et al 5 observed rates of NICU admission for >2 days after elective caesarean delivery were 6%, 6.1% for 38 and 39 weeks of gestation respectively which were comparable to our results.…”
Section: Discussionsupporting
confidence: 91%
“…However using the Chi square test (p=0.705) and there was no significant relation between weeks of gestation and the rate of NICU admission. In a study done by Glavind J et al 5 observed rates of NICU admission for >2 days after elective caesarean delivery were 6%, 6.1% for 38 and 39 weeks of gestation respectively which were comparable to our results.…”
Section: Discussionsupporting
confidence: 91%
“…The study 25 found no significant differences between the 2 groups in neonatal intensive care unit (NICU) admission within 48 hours of birth, NICU admission within 7 days, NICU length of stay, neonatal respiratory problems, neonatal treatment, or maternal outcomes. The results are summarized in Table 1.…”
Section: Week 38 Vs Week 39mentioning
confidence: 91%
“…After all, the average decrease in gestation duration after antenatal SSRI exposure was in the region of a few days, at the most, in the studies that did find differences between SSRI-exposed and unexposed pregnancies. A new study 25 provides some interesting insights in this regard.…”
Section: Week 38 Vs Week 39mentioning
confidence: 94%
See 2 more Smart Citations